Understanding the IBM TotalStorage open software family - Tretau, Roland (IBM, International Technical Support Organization, 2004)
This IBM Redbooks publication describes and explains the features and functions of the IBM TotalStorage Open Software Family, which is designed to help you simplify your storage infrastructure, optimize storage utilization, and adapt quickly and dynamically to the on demand world. The book introduces storage virtualization, on-demand solutions, and storage management software by explaining the concepts, architecture, and systems management features of the IBM TotalStorage Open Software Family and showing available complementary products. It will help you design solutions to protect data holdings from losses ranging from those caused by user error to complete site disasters. This easy-to-follow guide gives a broad understanding of the IBM TotalStorage Open Software Family software, the key technologies to know, and the solutions available to protect your business. It offers understanding of how the IBM TotalStorage Open Software Family solutions will work in heterogeneous environments including Windows, UNIX/AIX/Linux, OS/400, and z/OS platforms, and with such mission-critical applications as DB/2, Oracle, Lotus Domino, Exchange, mySAP.com, and many more.
Includes bibliographical references and index. - Print version record
Keywords: Memory management (Computer science); IBM computers; Gestion mémoire (Informatique); IBM (Ordinateurs)